1617f Coping with shiftwork: individual and team strategies for health and safety. (24th April 2018) - Dorrian, J; Centofanti, S; Colella, A; Devine, L; Dingle, C; Galindo, H; Pantelios, S; Brkic, G; Bull, C; Almond, T; Dhillon, V; Carskadon, MA; et al.
Abstract : Introduction: Shiftwork can negatively impact on performance, safety and health. Importantly, while some shiftworkers are profoundly affected, others cope very well. The aim of this project was to identify healthy shiftworkers (across measures of physical, behavioural and psychosocial health) in a group of Australian nurses and midwives, and to examine factors that may contribute to health across working life. Methods: This was a mixed methods study, combining survey, interview and biological measurements. Participating hospital nurses and midwives (n=96, f=85, age=44.3±12.6 y, shiftwork experience=18.9±12.7 y) completed the Standard Shiftwork Index, which includes measures of health, social, domestic and work disruption, and coping styles. Participants could also participate in an interview (n=22), and/or provide a saliva sample (n=45), to measure telomere length (if our DNA were shoelaces, telomeres would be the aglets). Results: Cluster analysis revealed a 'Healthier' and a 'Less Healthy' cluster, with significantly worse scores across all health variables (p<0.05). Controlling for gender, age and work hours, the odds of being 'Less Healthy' were significantly (p<0.05): reduced for experienced shiftworkers (≥20 y versus <20 y, OR=0.16); reduced by engaged coping style (OR=0.92); and increased by disengaged coping style (OR=1.20). Strategies for coping were aimed at promoting wakefulness/sleep at biologically difficult times, sustaining safe performance at work and while driving, and maintaining healthy diet, exercise and relationships. Strategies included the use of stimulants and sedatives, changes in composition/timing of food intake, changes in timing/distribution of sleep, advances/delays in undertaking safety-critical activities, and contributing to a culture of social support. Correlations between age and telomere length were negative in less experienced (<20 y, r =−0.22) and positive in more experienced (≥20 y, r =0.85) shiftworkers. Conclusion: Findings provided evidence of healthy ageing in experienced shiftworkers that was linked to coping style. Studying those who cope well provides an evidence-base for teaching successful behavioural strategies to improve worker health and safety.